Melatonin inhibits bovine viral diarrhea virus replication by ER stress-mediated NF-κB signal pathway and autophagy in MDBK cells - Zhao, Yi-Qing; Wang, Xue-Fei; Zhang, Jia-Lu; Wu, Yi (Frontiers in Cellular and Infection Microbiology, 2024)
Bovine viral diarrhea-mucosal disease (BVD-MD) is a contagious disease in cattle, caused by the bovine viral diarrhea virus (BVDV). This virus continues to spread globally, exerting pressure on both public health and the economy. Despite its impact, there are currently no effective drugs for treating BVDV. This study utilized Madin-Darby bovine kidney (MDBK) cells as a model to investigate the antiviral effects of melatonin against Bovine Viral Diarrhea Virus (BVDV) and its connection with endoplasmic reticulum (ER) stress. Our results show that melatonin can suppress BVDV proliferation in MDBK cells by modulating the endoplasmic reticulum (ER) stress-mediated NF-κB pathway and autophagy. Specifically, melatonin alleviated ER stress, inhibited the activation of IκBα and p65, regulated autophagy, and reduced the expression levels of pro-inflammatory cytokines. Further, when we treated BVDV-infected cells with the ER stress inducer thapsigargin, it led to significant activation of the NF-κB pathway and autophagy. Conversely, treating the cells with the ER stress inhibitor 4-phenylbutyric acid reversed these effects. These findings suggest that melatonin exerts its antiviral effects primarily through the PERK-eIF2α-ATF4 of ER stress-mediated NF-κB pathway and autophagy. Overall, our study underscores the potential of melatonin as an effective protective and therapeutic option against BVDV, offering insights into its anti-infective mechanisms.